A Medication Management Intervention for Patients and Families with SCI and ABI. (December 2020) - Oyesanya, Tolu O.; LeCroy, Tiffany; Sweatman, Mark; Hatch, Daniel; Nyankori, Liv; Kang, Yong; MacCaughelty, Tara; O'Pry, Laura; Johnson, Susan
The purpose of this study was to develop and test the efficacy of a pre-discharge, medication management intervention to improve perceived knowledge and perceived confidence for post-discharge medication management for rehabilitation patients with spinal cord injuries (SCIs) and families of patients with SCIs or acquired brain injuries (ABIs). We used a quasi-experimental, matched-pair design. Treatment participants ( n = 112) completed the intervention with pre- and post-tests assessing perceived knowledge and perceived confidence for post-discharge medication management. Control participants ( n = 95) enrolled at 60-days post-discharge. All participants ( N = 207) completed measures on perceived knowledge, perceived confidence, and medication management by phone at 60-days post-discharge. The intervention significantly increased treatment participants' perceived knowledge and perceived confidence from pre- to post-test. Sex, injury severity, and income were associated with primary outcomes. Treatment participants used more tools for medication management post-discharge. Our findings suggest that patients and family members may benefit from pre-discharge medication management interventions.